Occurrence of relapsing polychondritis with a rising cANCA titre in a cANCA-positive systemic and cerebral vasculitis patient. (15th February 2013) - Mattiassich, Georg; Egger, Markus; Semlitsch, Georg; Rainer, Franz
Abstract : Relapsing polychondritis (RP) is a relatively rare disorder, with a high death rate that affects cartilaginous structures. RP can be either primary or secondary as part of autoimmune syndromes. We present a case of RP in a 49-year-old man suffering from cytoplasmic antineurophil cytoplasmic antibodies (cANCA) positive vasculitis, admitted to our hospital with red swollen left ear and painful sternoclavicular joint and larynx. The patient was in remission from the vasculitis but manifested a high cANCA titre indicating vasculitis activity. With his high cANCA titre vasculitis, full manifestation of RP concomitantly occurred. After a successful cortisone treatment for RP, the patient received cyclophosphamide treatment for his vasculitis that resulted in a decrease in cANCA titre and full remission of his RP symptoms.